ALIH KODE INDONESIA-INGGRIS DALAM LIRIK LAGU “NOW I KNOW” KARYA KALEB J: ANALISIS SOSIOLINGUISTIK - Sofiyatunnida; Nadofah; Dewi Susanti (Universitas Muria Kudus, 2025)
This study examines the phenomenon of Indonesian-English code switching in the lyrics of the song